Menerapkan Etika Tanggung Jawab Hans Jonas dalam Membangun Kesadaran Ekologis Masyarakat Sekitar Sungai Bengawan Solo - Albertus Agung CP; Deny Firmanto (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2021)
Disasters and environmental crises threaten the sustainability of life on earth. All living things, including humans, must face rapid and significant climate change. Indonesia as an agricultural and maritime country faces difficult challenges. The life of the Indonesian people still depends a lot on the natural resources available in the archipelago. However, the lifestyle of the people has not shown the existence of an ecological awareness. Environmental destruction activities continue to occur in the country to this day. One of the damaged ecosystems is the Bengawan Solo river. The result is a decrease in water quality and biodiversity in the Bengawan Solo river. The surrounding community needs to be aware of the importance of an ecosystem that supports life together. Hans Jonas offers a new form of ethics that can be a trigger for human consciousness. He found an ethics of responsibility that is oriented not only to the present but also to the future. The starting point of his ethics is the heuristic of fear. The purpose of this study is to apply the ethics of Hans Jonas in fostering the community around the Bengawan Solo river. This study proves that Hans Jonas' ethical responsibility is relevant to building community awareness around the Bengawan Solo river towards ecological living.